Pengaruh Terpaan Akun Tiktok @Vmuliana Terhadap Pengetahuan Tentang Dunia Karir Untuk Followers - Karens Sabrina Purnasari; Dwi Prasetyo (LPPM Stikosa-AWS, 2022)
This study aims to determine the effect of exposure to the TikTok account @vmuliana on knowledge about the career world for followers. The theory used is the theory of S.O.R (Stimulus, Organism, Response). This theory is related to the message that is conveyed and the response that is raised. The type of research used is quantitative research with descriptive analysis method. By using a questionnaire in data collection. The sampling technique in this study used a purposive sampling technique. The population for this study are followers of the TikTok account @vmuliana and the sample taken is 100 respondents. Based on the research that has been done, the researchers conclude that there is a significant influence between TikTok @vmuliana content on career knowledge for followers. Associated with the influence of knowledge about the career world with a trend of influence of 73.1% and has a strong correlation of 0.855 and the coefficient of determination of 0.731.